Radiobiological modelling of gold nanoparticles radiosensitization effects in conventional and advanced radiotherapy techniques - Ab Rashid, Raizulnasuha (2021)
Improvement of radiotherapy techniques with nanotechnology is a promising strategy to overcome the limitations arises in conventional treatment such as lack of eradication selectivity and radioresistance characteristic of targeted tumour. Gold nanoparticles (AuNPs) is a subject of growing interest to induce radiosensitization effects with potential application in clinical radiotherapy. Despite numerous evidences, development and application of AuNPs as radiosensitizer require systematic and comprehensive experimental approaches to fully evaluate the radiobiological impact in radiotherapy. In this study, multiparametric investigations on the radiosensitization effects were conducted using different energies of clinical megavoltage photon, electron, and high-dose rate (HDR) gamma rays from Ir-192 source. In addition to conventional radiotherapy, advanced techniques using proton beam and monoenergetic synchrotron photon beam of kilovoltage energies were also employed. Comprehensive analysis using different radiobiological models and quantification methods were specifically examined. Influence of AuNPs size, concentration and types of cells on the radiosensitization effects were also elucidated including internalization, localization and cytotoxicity of AuNPs. Applicability of AuNPs for clinical conventional radiotherapy have been proven where radiosensitization effects have been observed especially for HDR brachytherapy that show better effects compare to electron and photon beam therapies. Substantially bigger impact of AuNPs radiosensitization have been confirmed for proton beam and monoenergetic kilovoltage synchrotron photon beam in concurrently with theoretical prediction. Validity of radiobiological models to describe the cell survival curve is dependent on the beam quality as well as quantification methods. Radiobiological models and their parameters also could be adopted as indicator to explain the mechanistic events in the AuNPs’ radiosensitization effects. The AuNPs size and concentration are found to influence the radiosensitization effects and different types of cells exhibit different radiosensitivity responses. The radiosensitization impacts of AuNPs with radiotherapy beams were considered with prior indication on the cellular internalization of AuNPs and the non-toxic concentration for optimal AuNPs application. As conclusion, effective radiosensitization by AuNPs could be achieved for megavoltage clinical radiotherapy, brachytherapy and advanced radiotherapy such as proton beam therapy and monoenergetic synchrotron beam radiotherapy. Precise radiobiological characterization drawn from radiobiological models may provide insight towards radiobiological impacts induced by AuNPs and standardization of quantification methods is crucial for highlighting suitable parameters for AuNPs clinical application. Clear directive recommendation from comprehensive preclinical data provided in this study may expedite the clinical translation of AuNPs for human application.